Crystallographic analysis of a novel aldo‐keto reductase from Thermotoga maritima in complex with NADP+. Issue 7 (1st July 2015) - Hou, Hai; Li, Ruiying; Wang, Xiaoyan; Yuan, Zhen; Liu, Xuemeng; Chen, Zhenmin; Xu, Xiaoling
<x xml:space="preserve">Abstract</x> Aldo‐keto reductases (AKRs) are a superfamily of NAD(P)H‐dependent oxidoreductases that catalyse the asymmetric reduction of aldehydes and ketones to chiral alcohols in various organisms. The novel aldo‐keto reductase Tm1743 from Thermotoga maritima was identified to have a broad substrate specificity and high thermostability, serving as an important enzyme in biocatalysis and fine‐chemical synthesis. In this study, Tm1743 was overexpressed in Escherichia coli BL21(DE3) cells with an N‐terminal His6 tag and was purified by Ni2+‐chelating affinity and size‐exclusion chromatography. Purified recombinant enzyme was incubated with its cofactor NADP+ and its substrate ethyl 2‐oxo‐4‐phenylbutyrate (EOPB) for crystallization. Two X‐ray diffraction data sets were collected at 2.0 and 1.7 Å resolution from dodecahedral crystals grown from samples containing Tm1743–NADP+–EOPB and Tm1743–NADP+, respectively. Both crystals belonged to space group P3121, with similar unit‐cell parameters. However, in the refined structure model only NADP+ was observed in the active site of the full‐length Tm1743 enzyme. Degradation of the N‐terminal vector‐derived amino acids during crystallization was confirmed by Western blot and mass‐spectrometric analyses.